Ultra-Compact Broadband Spot Size Converter Using Metamaterial Cell-Based Inverse Design - Sánchez-Sánchez, Alejandro; Pérez-Armenta, Carlos; Luque-González, José Manuel; Ortega-Moñux, Alejandro; Wangüemert-Pérez, J.Gonzalo; Molina-Fernández, Íñigo; Halir, Robert (Wiley, 2025)
With the expansion of silicon photonics from datacom applications into emerging fields like optical I/O, quantum and programmable photonics, there is an increasing demand for devices that combine ultra-compact footprints, low losses, and broad bandwidths. While inverse design techniques have proven very efficient in achieving small footprints, they often underutilize physical insight and rely on large parameter spaces that are challenging to explore, thereby limiting the performance of the resulting devices. Here a design methodology is presented that combines inverse design with a topology based on cells, each of which contains a subwavelength metamaterial. This approach significantly reduces the parameter space, while the inherent anisotropy of the subwavelength structures yields shorter devices. This technique is experimentally demonstrated with an ultra-compact spot size converter that achieves a ×24 expansion ratio times (from 0.5 to 12 𝝁m) over a length of only 7.2 𝝁m, with insertion losses of 0.8 dB across a measured bandwidth of 160 nm (up to 300 nm in simulation), surpassing the state-of-the-art by a wide margin.
Keywords: Anisotropía; Metamateriales; anisotropy; inverse design; metamaterial; spot-size; converter; subwave length